The influence of selected plant stimulants and mushrooms on the human body - Wojaczek, Marta; Polańska, Katarzyna; Kahan, Weronika; Poborowska, Dominika; Szafrańska, Weronika; Kras, Magdalena; Kosińska, Agnieszka; Niedbał, Piotr; Lelek, Katarzyna; Łata, Marcin (Quality in Sport, 2024)
INTRODUCTION In recent years, there has been an increase in the use of herbal stimulants around the world. Many people cannot imagine life without coffee, a cup of this drink is often a mandatory part of the day. As the world moves faster and faster, people are looking for a way to keep up with it. Therefore, more and more plant and mushroom stimulants appear on the market, which help people replenish energy deficiencies and meet the challenge of constantly living on the run. Selected stimulants, the benefits associated with their use, and side effects are described in the work below. THE AIM The aim of this work is to discuss the properties that stimulate the human body. We have selected less and more known plants and mushrooms, describing their properties, benefits of their use, side effects, and contraindications to their use. MATERIALS AND METHODS In this work, we describe the impact of substances that stimulate the human body contained in selected plants and mushrooms. A review of the literature available in the National Library of Medicine database at https://pubmed.ncbi.nlm.nih.gov and Google Scholar was conducted. The articles were searched using keywords such as herbs stimulants, fungi, side effects, adaptogens, and advantages. SUMMARY There are many plants and fungi in nature containing substances that have a beneficial effect on the human body. They improve brain function, reduce stress, and increase concentration. We often reach for them because we really need an additional energy booster in today’s world. However, it should be remembered that these agents in too high doses may also cause side effects. Therefore, these preparations should be selected individually, taking into account chronic diseases, conditions such as pregnancy and lactation, and medications taken.